Harmonization of Laws on Electronic Contracts Based on International Instruments for the ASEAN Economic Community - Andrew Betlehn (Global Legal Review, 2021)
Technological advancement has created new business practices such as utilizing electronic contracts. Utilization of electronic contracts, especially in international transactions, has pushed countries around the world to impose new regulations defining the legalities of electronic instruments. Challenges arise considering the global and borderless nature of electronic transactions faced with regulations of different countries that are not in sync with each other. This is especially apparent in Member States of the ASEAN Economic Community. This paper attempts to discover the ideal legal framework for electronic contracts in the ASEAN Economic Community. Based on the research and analysis, it has been found that there is a need for a harmonized legal framework regarding electronic commerce that can be adopted unaltered by Member States of the ASEAN Economic Community, which could be drafted by the ASEAN as an inter-governmental organization.